To Evaluate Structured Competency-Based Curriculum for Health Programs among Community Medicine Postgraduates: Mixed Method Approach - Rashmi Kundapur; Anusha Rashmi; Kumar Guru Mishra; Gunvanti Rathod; Meely Panda; Vikas Bhatia; Shyamala Ravikoti (Wolters Kluwer Medknow Publications, 2024)
Background: The postgraduate curriculum needs to be given a definite shape so as to make health programs more intensive and integrative. In the present scenario, most of the information is unclear and infrequent. A structured public health competency-based education is an important aspect to consider for integrative health care. Evaluate the structured competency-based curriculum (SCBC) prepared on health program matters. Methods: Mixed method model involving postgraduate students, faculties in community medicine departments of selected medical colleges and stakeholders from district administration. The SCBC was piloted and validated for use. The evaluation was then done based on pre- and posttest performance analysis, satisfaction survey, and questionnaires for reaction and learning components. Results: For a complete understanding of the program, students had to invest 52 hours of stipulated time. CBC assessment mean scores for a) problems in PHC and programmatic evaluation (78.9%) and b) identification of success and failure of programs (78.2%) were more than 75% mean score; whereas, assessment scores for topics on a) resource allocation and b) evaluation of program as write-up was 65% and 52%, respectively. As compared to the conventional method, the SCBC showed a critical evaluation score of 70% with a 0.001 significance level. Discussion and Conclusion: Students' narratives were that they could understand as well as integrate them better on the field. There was enhanced satisfaction and encouragement. Structured curriculum will also help in making learning more student-centric and go a long way in boosting their creativity.